Salaf Islamic Boarding School Learning Model in Facing New Normal - Abdul Khamid; Aida Dwi Rahmawati; Irhamudin (Jurnal Pendidikan Islam Al-Affan, 2021)
This study aims to determine the learning model apllied by the ustad/ustadzah at the Salaf al Manar in dealing with New Normal. This type of research used is a qualitative method. Data collection was carried out through field observations, interviews with questionnaires, and literature studies. The validity of data includes trus, transferability, dependability, and certainly. The findings in this study were that the learning model in PP. Salaf al Manar in the New Normal was accordance with the health protocol. Positive impacts included increasing science and technology, a spirit of learning, being more sensitive to the importance of cleanliness and health, planning and preparing for the learning process to be further improved with various innovations. Some of obtacles include the lack of medical equipment, many students have not returned to the hut, the arrival of regular students and isolation beforehand parents, and the emergence of more spending. Keywords: Learning Model, Salaf Islamic Boarding School, New Normal